Закон дисперсiї та ширина поверхневої акустичної моди в залежностi вiд концентрацiї адсорбованих атомiв - Peleshchak, R. M.; Seneta, M. Ya. (Publishing house "Academperiodika", 2018)
The dispersion law for elastic surface acoustic waves and the dependence of the surface acoustic mode width on the concentration of adsorbed atoms have been found. The calculations are carried out in the long-wave approximation for the interaction between the adatoms with regard for image forces and the non-local elastic interaction between the adsorbed and matrix atoms.